(untitled) (Global Journals of Research in Engineering, 2012)
A single feed compact rectangular microstrip antenna for quad band applications has been designed and developed. This antenna is incorporated by four L-shaped slot structure along the length on the patch. Four resonating frequencies are obtained at 1.845 GHz with return loss -21.19 dB, 2.59 GHz with return loss -17.69 dB, 3.29 GHz with return loss -21.56 dB and 4.825 GHz with return loss -22.31 dB. The size of the antenna has been reduced by 77.3% when compared to a conventional microstrip patch without slot. An extensive analysis of the return loss, radiation pattern and gain of the proposed antenna has been given in this paper. The characteristics of the designed structure are investigated by using MoM based electromagnetic solver, IE3D.The simple configuration and low profile nature of the proposed antenna leads to easy fabrication and multi frequency operation makes it suitable for the applications in Wireless Communication system.